A Reconnaissance Gravity and Magnetic Study in Aqra Plain - Ghaib, Fadhil A.; Abdul-Karim, Salih K.; Mohammad, Rashied J. (Sulaimani Journal for Pure and Applied Sciences, 2002)
A gravity and magnetic survey was carried out as a first study of this kind in Aqra plain area (NE of lraq). The survey occupied 116 gravity stations a long the main roads, as well as some sub roads. In addition that 29 magnetic readings along the main road between Aqra town and Bardarash village where taken. The aim of this work is to obtain the main subsurface, shallow and deep structural units. The regional and residual anomalies for both gravity and magnetic data have been analysed qualitatively were related to the expected geological features. The study showed that the basement rocks slope towards north and northeast with a depth of a bout 6-7km.
Keywords: Aqra; Gravity; Magnetic